Patterns of Pediatric Inflammatory Bowel Disease and Effectiveness of StepUp Therapy - Tahir Mahmood, Lubna Manzoor, Salman Ali, Zahid Rashid, Nasir Khan, Fouzia Ali, Firdous Adam, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pediatric inflammatory bowel disease (IBD), encompassing Crohn's disease (CD) and ulcerative colitis (UC), presents unique challenges due to its early onset and potential for rapid progression. This study aims to delineate the clinical patterns of pediatric IBD and evaluate the effectiveness of step-up therapy in disease management. A cohort of 150 children diagnosed with IBD was prospectively analyzed over a 24-month period